District cooling pipes. Bonded single pipe systems for directly buried cold water networks. Factory made pipe assembly of steel or plastic service pipe, polyurethane thermal insulation and a casing of polyethylene Part 1, (4th August 2020) - British Standards Institution
No abstract available